Gallbladder Cryoablation: Clinical and Technical Considerations - McGregor, Hugh (Digestive Disease Interventions, 2022)
As many as 500,000 cholecystectomies are performed per year in the United States. Frail patients are at higher risk from cholecystectomy, with reported postoperative complication and mortality rates as high as 31 and 5% in patients older than 75 years. Percutaneous cholecystostomy drainage is commonly employed in high-risk patients with cholecystitis, with over 12,000 cases performed annually. Cholecystostomy, however, is not a definitive treatment, with up to 30% of patients having a recurrent episode of cholecystitis within 4 months after tube removal. Gallbladder cryoablation has emerged as a minimally invasive procedure that achieves transmural gallbladder wall necrosis in a single session resulting in gallbladder fibrosis and involution. Early clinical data have been promising, with reported technical success of 86% and clinical success of 100% at up to 500 days of follow-up. Several challenges and unknowns remain, however, including optimal patient selection and procedural technique, the potential need for adjunct procedures to occlude the cystic duct, the implications of the immunostimulatory effects of cryoablation, and the impact of the presence of gallstones on outcomes. This article reviews the rationale behind gallbladder cryoablation, updates early clinical outcomes, and discusses the challenges that remain for the adoption of the technique for the treatment of benign gallbladder disease.
Keywords: gallbladder; cryoablation; cholecystitis